The association between aldosterone and lipid profiles in patients with primary aldosteronism - Ning-Peng Liang; Kun-Rui Rao; Ming Hu; Ru-Yi Bao; Jian-Wei Liu; Ze-Qun Lai; Hong-Jin Zhang; Huang Zhang; Meng-Bo Wu; Xiang-Tao Zhang; Yi-Fei Dong (Scientific Reports)
Abstract Previous studies have yielded inconsistent findings regarding the comparison of lipid profiles in patients with primary aldosteronism (PA) and essential hypertension (EH), and there is a limited understanding of the association between plasma aldosterone concentration (PAC) and lipid profiles across various populations. 270 patients with PA and 598 patients with EH diagnosed at the Second Affiliated Hospital of Nanchang University from January 2020 to June 2021 were consecutively included. After 1:1 propensity score matching by sex, age, and body mass index (BMI), 267 PA and 267 EH patients were ultimately enrolled in the study. The relationship between PAC and lipids was explored. Compared with EH patients, PA patients showed significantly lower levels of total cholesterol (TC) (P = 0.003), low-density lipoprotein cholesterol (LDL-C) (P < 0.001) and non-high-density lipoprotein cholesterol (Non-HDL-C) (P = 0.014). Log TC (P = 0.0256), log triglyceride (TG) (P = 0.0497) and log Non-HDL-C (P = 0.0184) levels were negatively correlated with log PAC in PA patients. Consistently, these lipids yielded similar results with aldosterone/renin ratio (ARR). However, the correlation does not exist in EH patients. The levels of TC, LDL-C and Non-HDL-C were significantly lower in PA than in EH patients. And a significant independent inverse association between log TC, log TG, log Non-HDL-C, and log PAC levels in PA patients. However, the above associations were not always present in clinically matched EH patients.